Maternal age and asthma in Latino populations. Issue 11 (6th July 2016) - Abid, Z.; Oh, S. S.; Hu, D.; Sen, S.; Huntsman, S.; Eng, C.; Farber, H. J.; Rodriguez‐Cintron, W.; Rodriguez‐Santana, J. R.; Serebrisky, D.; Avila, P. C.; Thyne, S. M.; et al.
Summary: Background: Younger maternal age at birth is associated with increased risk of asthma in offspring in European descent populations, but has not been studied in Latino populations. Objectives: We sought to examine the relationship between maternal age at birth and prevalence of asthma in a nationwide study of Latino children. Methods: We included 3473 Latino children aged 8–21 years (1696 subjects with physician‐diagnosed asthma and 1777 healthy controls) from five US centres and Puerto Rico recruited from July 2008 through November 2011. We used multiple logistic regression models to examine the effect of maternal age at birth on asthma in offspring overall and in analyses stratified by ethnic subgroup (Mexican American, Puerto Rican and other Latino). Secondary analyses evaluated the effects of siblings, acculturation and income on this relationship. Results: Maternal age < 20 years was significantly associated with decreased odds of asthma in offspring, independent of other risk factors (OR = 0.73, 95% CI: 0.57–0.93). In subgroup analyses, the protective effect of younger maternal age was observed only in Mexican Americans (OR = 0.53, 95% CI: 0.36, 0.79). In Puerto Ricans, older maternal age was associated with decreased odds of asthma (OR = 0.65, 95% CI: 0.44–0.97). In further stratified models, the protective effect of younger maternal age in Mexican Americans was seen only in children without older siblings (OR = 0.44, 95% CI: 0.23–0.81). Conclusion and Clinical Relevance: In contrast to European descent populations, younger maternal age was associated with decreased odds of asthma in offspring in Mexican American women. Asthma is common in urban minority populations but the factors underlying the varying prevalence among different Latino ethnicities in the United States is not well understood. Maternal age represents one factor that may help to explain this variability.